Mechanical thrombectomy with the non-attaching remote thrombus-aspiration (NARA) technique: a technical note - Masashi Kotsugi; Ai Okamoto; Yudai Morisaki; Ryosuke Maeoka; Shohei Yokoyama; Shuichi Yamada; Ichiro Nakagawa (World Neurosurgery: X, 2025)
Background: A direct aspiration, first-pass thrombectomy (ADAPT) has become the standard technique for thrombus removal and involves contact aspiration with a large-bore suction catheter. However, thrombus retrieval can prove difficult in cases where the thrombus volume is large and occlusion extends across branches. Further, access to the thrombus is frequently complicated by the age of the affected population. Methods: We present two cases in which the thrombus was remotely retrieved with the non-attaching remote thrombus-aspiration (NARA) technique to indirectly apply pressure to the thrombus by maintaining negative pressure through a suction catheter while completely blocking antegrade blood flow. Results: Although the aspiration catheter was not guided to the thrombus, aspiration was started under proximal flow control with inflation of the guiding balloon. When aspiration pressure reached the thrombus, the aspirating catheter showed no retrograde blood flow. Both thrombi were retrieved in a single procedure, and blood flow (Thrombolysis in Cerebral Infarction grade 3) was restored in each case. Conclusions: We achieved remote thrombus retrieval using the NARA technique in two cases. Remote thrombus retrieval is feasible even if the tip of the suction catheter cannot reach the thrombus. This technique may be useful in difficult-to-access cases.